Revitalization of People’s Market: A Case Study of Jibama Market, Jayawijaya Regency - Henderina Morin (Formosa Journal of Science and Technology, 2023)
The study was conducted with the aim of discussing the Jibama people's market revitalization policy as an effort to improve people's welfare in Jayawijaya Regency, Papua Mountains Province. The method used is a library approach. Sources of data come from various sources of literature that are relevant to the topic under study. Data analysis was carried out through three stages: data collection, data presentation, and a final conclusion. The results of this study indicate that Jibama market traders are both local traders and non-local traders (immigrants). In 2017, the number of selling booths was 6 with 50 kiosks. The revitalization of the Jibama Market was carried out in 2018. Nevertheless, it is important to reorganize the Jibama people's market, mainly related to market order and security. This is intended to make market traders more organized and tidy.